Osmanlı Dönemi’nden İngiliz İdaresine Kıbrıs Türk Temel Eğitimi’nin Modernleşmesi ve Toplumsallaşması / From Ottoman Period to English Administration Modernization and Socialization of Cyprus Turkish Basic Education - Özkul, Ali Efdal; Tufan, Hüseyin; Özsezer, Mete (Journal of History Culture and Art Research, 2017)
Abstract Changes in the primary education programme during the transition period from the agricultural society to the industrial society of the Turkish Cypriots in the Ottoman and British administrations in Cyprus were evaluated in terms of educational programs, number of students and modern agriculture course in this study. Following the Ottoman conquest of island, the educational institutions were also regulated like every other organisation in the island according to the needs. After the British took over the island administration from the Ottoman State, they maintain some of the applications from the old administration as well as replacing some of them according to their own administrative and administrative understandings. During the British administration, the education in the Turkish Cypriot community had switched from the religion intensive curriculum to modern education. This study aimed to reflect the details of new education system during the British administration in the island. In addition, as an example of the socialization of education, the increase in the number of students in education and the situation of female students in this increase have been emphasized in this study. The information obtained by using the first-hand resources of the research period, Blue Book, and education reports, is presented. As a result, the changes made in the Turkish Cypriot Education system have affected the Turkish Cypriot community socially, culturally and politically. Öz Kıbrıs’ta Osmanlı ve İngiliz idaresinde Kıbrıslı Türklerin tarım toplumundan sanayi toplumuna geçiş sürecinde ilköğretim programında oluşan değişimlerin bu araştırmada eğitim programları ve öğrenci sayısı açısından değerlendirilmesi amaçlanmıştır. Osmanlı Devleti’nin adayı fethetmesinden sonra adadaki her kurum gibi eğitim teşkilatını da ihtiyaçlara göre düzenlemiştir. İngilizler ada yönetimini Osmanlı Devleti’nden devraldıktan sonra, eski idareden kalan bazı uygulamaları devam ettirirken, bazılarının yerine kendi idari ve yönetim anlayışlarına göre düzenlemişlerdir. İngiliz idaresi sürecinde Kıbrıslı Türklerde eğitim dini ağırlıklı müfredattan modern eğitime geçmiştir. Yapılan araştırmada İngiliz döneminde adada uygulanan yeni eğitim sisteminin detayları ortaya konulmaya çalışılmıştır. Ayrıca çalışmada eğitimin toplumlaşmasına örnek olarak eğitimdeki öğrenci sayılarındaki artışın ve bu artış içerisinde kız öğrencilerin durumuna dikkat çekilmiştir. Söz konusu araştırmada döneminin birinci el kaynakları olan Blue Book’lar ile dönemin eğitim raporlarından faydalanılmıştır. Sonuç olarak Kıbrıs Türk Eğitim sisteminde yapılan değişikler Kıbrıs Türk Toplumunu sosyal, kültürel ve siyasi olarak etkilemiştir.